Structural, Morphological, Optical and Dielectric Studies of RE3+ Doped CoFe2O4 - Boddolla, Sathish; Ravinder, D (Journal for Research in Applied Sciences and Biotechnology, 2024)
Cobalt ferrite nanoparticles, both undoped and Eu³⁺-doped, with the formula CoEuxFe2-xO4 (where x = 0.00 and 0.10), were produced using the citrate gel auto-combustion technique. X-ray diffraction confirmed the successful formation of the phase and the purity of the synthesized nanoparticles. The morphological analysis was conducted using scanning electron microscopy (SEM). The optical properties of cobalt ferrite were analyzed using UV-Vis spectrometer. Dielectric properties, such as the real part of the dielectric constant and loss tangent, were evaluated using an LCR meter. Doping cobalt ferrite nanoparticles with europium resulted in a significant improvement in charge storage and transport characteristics.